PENGARUH FINANCIAL PERFORMING TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH GREEN SUPPLY CHAIN MANAGEMENT (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2018-2022) - Jauhari Ibnu Hamdani; Dwi Nita Aryani (POLITEKNIK LP3I JAKARTA, 2024)
Investors will consider financial performance when choosing an investment. Financial performance can continue to improve with the implementation of the right business strategy, thereby increasing company value. the purpose of this study was to test and analyze the effect of current ratio, return on investment, and green supply chain management on firm value, as well as to test and analyze whether green supply chain management can moderate the effect of current ratio and return on investment on firm value. This research uses quantitative research. The data source in this study was taken from secondary data, namely annual reports obtained from the Indonesia Stock Exchange (IDX). The description of the population in this study is a manufacturing company in the food and beverages sub-sector listed on the Indonesia Stock Exchange (IDX) in 2018-2022. Based on the research results, it is known that CR has a positive and significant effect on firm value, ROI has a positive and significant effect on firm value, GSCM has a positive and significant effect on firm value. Then GSCM is not able to moderate the effect of CR and ROI on firm value. Key words: Current ratio, Return On Investment,Green Supply Management